Trust, Victimization, and Disorder in Mexicans’ Perception of Insecurity - Gómez Martínez , Martina Livier (Consorcio de Universidades Mexicanas A.C., 2019)
The study of fear of crime is very important in the field of criminology. Previous international studies found that the relationships between fear of crime models and the perception of safety exist in people no matter where they are. Therefore, in this paper three factors were taken into consideration: victimization, trust and disorder to examine its influence on the perception of safety in Mexicans. Using data from the National Survey of Victimization of Security Perception 2016 of the National Institute of Statistics and Geography in Mexico (INEGI), a multiple regression analysis was conducted in which it was found that these factors have a direct impact on the feeling of citizens’ insecurity. Likewise, according to previous studies of fear of crime, Mexican population also shows a tendency to have effects of these models. Particularly, their perception of safety decreases when they have been previously victimized and when there is social disorder in their communities.